Специализированная геоинформационная система РАПИД: структура, технология, задачи - Бусыгин, Б.С.; Никулин, С.Л. (Геоінформатика, 2016)
Изложены основные сведения о геоинформационной системе (ГИС) РАПИД. Описана геоинформационная технология, которую реализует система. ГИС РАПИД ориентирована на совместную обработку и анализ наземных и космических данных, позволяет решать широкий круг задач наук о Земле на общих методических принципах. Система объединяет инструментарий универсальных ГИС с математическим аппаратом Data Mining, что дает возможность интегрировать разнотипные многоуровневые геоданные и извлекать из них новую информацию. Представлена информация о функциональных возможностях и структуре системы, дан пример практического применения технологии РАПИД. Показано, что при использовании системы и технологии повышается эффективность интегрированного анализа разнородных геоданных, решения задач природо- и недропользования, сокращаются затраты времени и средств. Викладено основні відомості про геоінформаційну систему (ГІС) РАПІД. Описано геоінформаційну технологію, яку реалізує система. ГІС РАПІД орієнтована на спільну обробку й аналіз наземних і космічних даних, що дає змогу вирішувати широке коло завдань наук про Землю на загальних методичних принципах. Система поєднує інструментарій універсальних ГІС з математичним апаратом Data Mining для інтегрування різнотипних багаторівневих геоданих і отримання нової інформації. Наведено інформацію про функціональні можливості й структуру системи і приклад практичного застосування технології РАПІД. Показано, що за застосування системи і технології підвищується ефективність інтегрованого аналізу різнорідних геоданих і вирішення завдань природо- й надрокористування, скорочуються витрати часу й коштів. Purpose. The purpose of the paper is to describe the functionality and structure of the geographic information system RAPID (created by GIS Department of the National Mining University) and GIS technology which the system implements. The system focuses on the integrated processing and analysis of terrestrial and space-based data, and allows us to solve a wide range of problems of nature and mineral resources management using common methodological principles. The system unites universal GIS tools with mathematical apparatus of Data Mining that enables us to integrate heterogeneous multi-level geospatial data and extract new information.
Design/methodology/approach. The developed system uses a variety of methods of mathematical statistics, image processing, lineament analysis, as well as specific methods of Data Mining — classification, pattern recognition, sequential analysis, association rules searching and others. It permits to extract new information from large volumes of heterogeneous data. The geoinformation technology based on the RAPID GIS implements the principle of multivariate problem solving with the help of simulation and computational experiments. It is aimed at uncovering direct links between the spatial arrangement of the studied objects/phenomena and structure of the data describing them.
Findings. The developed system is a versatile tool of mineral deposits prediction, territories mapping, monitoring and forecasting of various geological and ecological situations, eds. The paper gives an example of the practical application of the RAPID technology for gold objects prediction within the Western Uzbekistan territory. The aim was to locate sites promising for new gold objects detection. Source data were presented as high-precision QuickBird-2 space images, geophysical fields and geological information. Some promising areas were detected by applying procedures of supervised classification, lineament analysis, and methods of geological structure complexity assessing. Their area is estimated to be 5,1 % of the total area of the investigated territory.
Practical value/implications. The RAPID GIS has been used successfully by a number of geological enterprises of Ukraine, Uzbekistan, Kazakhstan, and Russia. Experience has shown that its use can improve the effectiveness of integrated analysis of heterogeneous multi-level geospatial data to reduce time and costs, and provides experts and researchers with a powerful and flexible tool for investigating, in particular, tasks of ecology and mineral resources management. At the moment the system has no analogs in Ukraine and possesses a number of functions that such widely known products as Geosoft/Oasis montaj, ArcGIS, Erdas Imagine, ENVI, and eCognition are lacking.